Unraveling Evolutionary Paths: Genomic Divergence and Geographic Secrets of Cylindrospermopsis and Sphaerospermopsis - Nooblath, Reno S.; Gomes, Daniel H.; Almeida, Sintia S.; Abreu, Vinícius A. (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2024)
This study aims to investigate the biological diversity of 21 genomes of Cylindrospermopsis and 6 genomes of Sphaerospermopsis belonging to the family Aphanizomenonaceae using bioinformatics methods in comparative genomics. The comparative analysis of the lineages of the groups From the Americas, Non-Americas and Sphaerospermospsis revealed conserved central genome but with different accessory genomes by geographic region. The variations observed in the organization of saxitoxin and cylindrospermopsin genes in the accessory genome of Cylindrospermopsis raciborskii from the Americas and NonAmericas, suggests in the future the formation of a new taxonomic group, due to independent evolutionary trajectories.